2019
DOI: 10.1136/bcr-2019-229612
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pulmonary blastomycosis with high-dose liposomal amphotericin B in a patient receiving extracorporeal membrane oxygenation

Abstract: Blastomycosis-associated acute respiratory distress syndrome (ARDS) has a rare incidence. We report the case of a 29-year-old man with blastomycosis-associated ARDS receiving extracorporeal membrane oxygenation and managed with high-dose liposomal amphotericin B. This case illustrates the importance of timely diagnosis of pulmonary blastomycosis and appropriate dosing of antifungal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Liposomes functionalized with groups, such as mannose, have been found to increase alveolar cell uptake, whereas attaching them with specific antibodies increases tissue targeting and local drug release in the lungs [ 151 , 152 ]. In several studies, liposomes have been shown to deliver drugs like amphotericin B and paclitaxel in pulmonary diseases [ 153 , 154 ]. The liposomal formulation of N -acetylcysteine has shown improved prophylactic efficacy against lipopolysaccharide-induced lung injuries in animal models displaying ARDS pathology [ 155 ].…”
Section: Nanotechnology-based Drug Delivery Systems In Ardsmentioning
confidence: 99%
“…Liposomes functionalized with groups, such as mannose, have been found to increase alveolar cell uptake, whereas attaching them with specific antibodies increases tissue targeting and local drug release in the lungs [ 151 , 152 ]. In several studies, liposomes have been shown to deliver drugs like amphotericin B and paclitaxel in pulmonary diseases [ 153 , 154 ]. The liposomal formulation of N -acetylcysteine has shown improved prophylactic efficacy against lipopolysaccharide-induced lung injuries in animal models displaying ARDS pathology [ 155 ].…”
Section: Nanotechnology-based Drug Delivery Systems In Ardsmentioning
confidence: 99%
“…An increasing number of institutions have reported experience in using extracorporeal membrane oxygenation (ECMO) for severe blastomycosis-associated ARDS. 58,60,61,[108][109][110][111][112][113][114] Good outcomes have been reported in many cases 58,61,115 ; however, the fact that most published experience is from individual case reports or small case series warrants interpreting these results with caution because of the potential for reporting bias. One case report suggested that liposomal amphotericin B became sequestered in and occluded the ECMO circuit, 116 but other published reports have not noted this complication.…”
Section: Difficult-to-treat Complications Of Blastomycosismentioning
confidence: 99%
“…One case report suggested that liposomal amphotericin B became sequestered in and occluded the ECMO circuit, 116 but other published reports have not noted this complication. 60,108,[110][111][112][113][114] In another case report, a patient with blastomycosis-associated ARDS requiring ECMO deteriorated despite standard dosing of liposomal amphotericin B (5 mg/kg daily), but seemed to respond to a higher dose (7.5 mg/kg daily was needed for clinical response). 113 In light of these concerns, we recommend treating blastomycosis-associated ARDS in patients receiving ECMO with liposomal amphotericin B dosed at 7.5 mg/kg daily.…”
Section: Difficult-to-treat Complications Of Blastomycosismentioning
confidence: 99%
See 2 more Smart Citations